A produção do espaço no centro histórico de Ouro Preto: processo de esvaziamento residencial e as práticas entre o percebido e o vivido - Edson Fialho de Rezende (2018)
This dissertation aims to analyze the World Cultural Heritage city of Ouro Preto, in Minas Gerais. The study focuses on urban space formation, starting from the residential emptying of urban centrality. This reality drives the deflection of values attributed to such spaces and also the weakening of socio-spatial practices in contemporary times. In the wake of the social, political and economic perspectives applied to the city, our chosen theoretical framework was guided by the philosophical principles presented by Henri Léfèbvre, based on interpretations of conceived, perceived and lived spaces. We start by presenting a theoretical analysis of Cultural Heritage around the world in order to understand the conceived space, as Cultural Heritage was shaped in Brazil, finding the synthesis of a precursory experience of national ideology institutionalization in Ouro Preto. Next, we present a descriptive reading of the spatial frame contemplated in this research which confirmed the practices of occupation of residential buildings and evidenced other increasingly capitalism oriented processes of space formation in the urban center of the Heritage city. Finally, we approach the understanding of everyday interactions between the local resident and the city through socio-spatial practices, according to the Lefebvrian theory of perceived and lived space. When we reflect upon the principles of Historic Urban Landscape preservation and the Right to the City we acknowledge that the intersection between the preservation of the patrimony and the dynamics of urban centrality is necessary. Thus, we conclude that the process of residential emptying is a foretaste of the new urban values in contemporary times. Faced with this, such reality must claim the converging of the preservation of Ouro Preto to the profuse sense of urbanity and urban life, with the possibilities of guaranteeing the local inhabitants have the right and the duty to elaborate the production of their own space in the heritage city.